Procedure Training Workshop for Internal Medicine Residents that Emphasizes Procedural Ultrasound: Logistics and Teaching Materials - Lisa Vande Vusse; Amanda Shepherd; Brittany Bergam; Justin Andros; Amy Morris (Association of American Medical Colleges, 2020)
Introduction Early formal instruction in procedural skills may increase the frequency with which residents perform procedures in the clinical setting. This workshop trained internal medicine residents in ultrasound skills and manual skills required to perform procedures common on medicine wards and required for board eligibility. Methods Since 2016, our internal medicine residency program has executed three annual half-day workshops for interns during orientation, before clinical duties began. Prior to the workshop, we directed interns to relevant educational resources in the form of online modules and videos. At the workshop, trainees rotated in small groups through facilitated stations to learn basics of procedural ultrasound and to practice manual tasks performed during paracentesis, thoracentesis, lumbar puncture, and peripheral intravenous catheter placement. We administered questionnaires before and immediately after the workshop and used Wilcoxon signed rank tests to compare self-assessed independence and confidence. Results Two hundred four interns with little prior procedural training participated in the workshop. Most participants (85%) indicated that orientation was the best timing for this training experience when compared to later options. Confidence and independence increased for ultrasound-marked thoracentesis, paracentesis, and peripheral intravenous catheters and for lumbar puncture without ultrasound. Discussion This internal medicine intern orientation workshop on procedures and procedural ultrasound was well received and increased participants' confidence and sense of independence. This publication contains materials needed to reproduce the training experience.